Bibliometric Analysis in Event Sponsorship Marketing Strategy in Increasing Brand Exposure - Susanto, Dimas Jayamahe; Ahmad; Astutiningsih, Lucya Friska (SMARTINDO, 2024)
Purpose – This paper aims to provide a general overview of brand exposure for a brand in sponsorship marketing methods. Special attention is paid to articles directly related to Marketing, Brand Exposure, and Sponsorship Methodology – Bibliometric analysis was carried out on 68 documents extracted from the WOS database, using VOS viewer software. Findings – This literature has achieved great development and implemented different research lines. A special analysis of the academic literature on Brand Exposure in the field of Marketing and Sponsorship has been carried out in Brand Exposure. Implication – The development of scientific knowledge about Brand Exposure has made this the center of business management studies regarding the focus on marketing sponsorship of a brand at an event. Originality – Several previous studies have provided a systematic review of the literature using different approaches, but did not explain in detail the structure of the effect of brands on sponsorship itself dictating the need for further development. Conclusion – The relationship between Brand Exposure and Sponsorship. Sponsorship carried out by a brand can increase brand awareness, visibility, and brand recognition. By supporting a popular event or cause, sponsors can expand their brand's reach and create an emotional connection with consumers